EVALUATION OF THE ANTIPSYCHOTIC PROPERTY OF MORIN AND ITS MECHANISMS OF ACTION IN EXPERIMENTAL MICE (2018)
Psychosis is a chronic neuropsychiatric disease characterised by severe behavioural perturbations. Current drugs used in the management of the disease are associated with serious side effects. Therefore, compounds with psychotropic-antioxidant effects are currently being sought as alternatives. Morin, a naturally-occurring neuroactive flavonoid isolated from Morusalba possesses strong psychotropic and antioxidant properties, however the mechanism of the antipsychotic property has not been fully elucidated. This study was designed to investigate the antipsychotic-like activity of morin and its mechanisms of action in mice. Morin was administered intraperitoneally to male Swiss mice. Ninety mice randomised into 6 groups of each experiment (n=5): vehicle (normal saline, 10mL/kg), morin (25, 50, 100mg/kg), haloperidol (1mg/kg) and risperidone (0.5mg/kg); were pre-treated to assess the acute antipsychotic effects of morin on apomorphine-(2mg/kg), ketamine-(10mg/kg) induced stereotypes and woodblock-catalepsy test. For the chronic studies, fifty mice were given preventive treatments (n=5) with morin (100mg/kg/day), haloperidol (1mg/kg/day), risperidone (0.5mg/kg/day), or vehicle for 14 days prior to injection of ketamine (20mg/kg/day) from the 8th-14th day. For the reversal treatment, animals received ketamine for 14 days prior to the treatments. The antipsychotic and neuroinflammatory effects were also assessed in 25 mice following pretreatments with vehicle, morin, haloperidol and risperidone, in combination with lipopolysaccharide (0.1mg/kg/day) induced neuroinflammation for 14 days prior to ketamine (20mg/kg/day) treatment from the 8th-14th day. Schizophrenia-like behaviours in all chronic studies were evaluated using open-field, social-interaction and Y-maze tests. Thereafter, brain biomarkers of oxidative/nitrergic stress were determined, spectrophotometrically in specific-brain regions (striatum, prefrontal cortex and hippocampus) in preventive-reversal and neuroinflammatory studies. Specific-brain regions of dopamine, glutamate and serotonin concentrations, Glutamic Acid Decarboxylase-67 (GAD67), Brain-Derived Neurotrophic Factor (BDNF) and gp91-phox expressions were measured in the preventive-reversal study using ELISA or immunohistochemistry. Brain Tumor Necrosis Factor-alpha (TNF-α),interleukin-6 levels, cyclooxygenase-2 (COX-2) and Nuclear Factor-κB (NFκB) expressions were determined in the neuroinflammatory study using ELISA or immunohistochemistry. Dendritic arborization of the cortical pyramidal neurons of lipopolysaccharide-ketamine treated mice was assessed using silver-impregnation stain. Data were analysed using descriptive statistics and ANOVA at α0.05. Morin (25, 50, 100mg/kg) significantly suppressed stereotypy induced by apomorphine (23.4, 34.5 and 60.1%) and ketamine (33.7, 73.4 and 83.4%) relative to controls,and was devoid of extrapyramidal side effects in catalepsy test.Morin (100mg/kg) prevented and reversed ketamine-induced social and cognitive deficits relative to controls and ketamine-induced hyperlocomotion (61.6±5.2 vs109.8±5.3; 47.0±6.1 vs103.2±4.5), respectively. Morin prevented and reversed altered dopaminergic, glutamatergic, GABAergic and serotonergic neurotransmissions in the striatum, prefrontal cortex and hippocampus, respectively. Morin increased BDNF, glutathione, and decreased malondialdehyde, nitrite levels and pg91-phox expressions in the three brain regions. Morin reduced TNF-α (124.7±8.6 vs212.7±9.4; 117.3±9.7 vs278.5±13.9 pg/g tissue) in the striatum and prefrontal cortex, and morin also reduced interleukin-6 (321.3±24.2 vs704.7±26.3, 295.1±19.7 vs581.3±47.4 pg/g tissue) in the prefrontal cortex and hippocampus. It also reduced COX-2 and NFκB expressions in the three brain-regions, and increased dendritic arborization of the cortical-pyramidal neurons. Morin demonstrated antipsychotic-like activity via mechanisms related to modulation of neurotransmitters, enhancement of neurotrophin, inhibition of oxidative/nitrergic stress and neuroinflammation.